The role and importance of banks in increasing investment activity in Khorezm region (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2024)
The very fact that the concept of investments, as the main economic concepts of modernization of the economy, has entered our lives today widely and quickly shows its essence and importance, necessity, and creates the need to reveal it. This concept brings with it the discovery of many new concepts and economic knowledge, such as the concept of investment projects, the implementation and financing of investment projects, their technical and economic justification and expertise, project analysis, evaluation and monitoring of the effectiveness of projects, and their discovery in our economic life today. making us realize how important it is. If we consider that today every educated person understands that the future development of the world economy, including the economy of Uzbekistan, mainly depends on investments, then the widespread attraction of investments, especially foreign investments, to the economy of our republic today is a part of the economic reforms that are being carried out in our country. it is not difficult to understand that it has become an important basis for ensuring its effective implementation.